Screening for marine-derived inhibitors of Chikungunya virus replication - Lillsunde, Katja-Emilia; Helsingin yliopisto. Farmasian laitos ([Katja-Emilia Lillsunde], 2012)
Referat
Keywords: farmasia; farmaci